Argentina: Economic Turbulence, Social Polarization and Political Realignment - De Luca, Miguel; Malamud, Andrés (Revista de Ciencia Política, 2020)
The 2009 mid-term elections produced a complex scenario for President Cristina Fernández de Kirchner. By winning just one third of the vote, she lost the majority in the House and the Senate – in the latter case due to divisions in the ruling coalition rather than because of the electoral results. Social distress nurtured by government behavior contributed to galvanizing a previously fragmented opposition. Hence, two electoral coalitions with non-rival territorial strongholds managed to defeat the incumbent party in the main districts. The economy resented both the global crisis and domestic mismanagement; although a meltdown was avoided, fiscal frailty persists due to a lack of alternative credit sources. Confronted with divided government, high social polarization and a stumbling economy, the President faces her next two years without visible inclination towards political accommodation or credible prospects of reelection.